PAxSPL: A feature retrieval process for software product line reengineering. (31st May 2019) - Marchezan, Luciano; Macedo Rodrigues, Elder; Bernardino, Maicon; Paulo Basso, Fábio
Summary: Software product lines (SPLs) are a well‐known solution to systematically create reusable software products. Among the approaches to create an SPL, the extractive approach is usually used when the organization already has a set of similar systems. These systems are analyzed to extract, categorize, and group their common and variant features throughout the SPL reengineering process. As there are different scenario variables, such as available artifacts and team experience, the activities and techniques used to perform these tasks may change. This may increase the effort and decrease the quality of retrieved features when users with low experience in SPL reengineering perform such tasks. However, there is a lack of a process supporting these tasks considering different scenarios. Therefore, we specify theP repare, A ssemble, and Ex ecute Process for SPL Reengineering (PAxSPL), a process that provides support to prepare, assemble, and execute feature retrieval throughout the analysis of documentation and team experience. To initially evaluate PAxSPL, we conducted and reported an exploratory case study in a real development environment. The results indicated that our proposal helps in the assembly of a feature retrieval process according to user needs. Results were important to identify points for improvement in PAxSPL. We also could use the information gathered to improve the guidelines and provide this information to be used as basis of comparison for future users.